2018
DOI: 10.1159/000495986
|View full text |Cite
|
Sign up to set email alerts
|

Over-the-Counter Herbal Weight Loss Supplements in Egypt: Label Claim, Microbiological and Pharmaceutical Quality, and Safety Assessments

Abstract: Objectives: Nutraceuticals are advertised and sold with the label claim of being natural and safe herbal products. Due to the absence of clear regulations and guidelines for safety assessments of these products, nutraceuticals are commonly adulterated in order to increase sales. The objective of the current study was to design a comprehensive evaluation system to assess the safety, efficacy, authenticity according to label claim, and pharmaceutical quality of herbal slimming products in between 2015 and 2017. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…This drug is often found alongside sibutramine as an illegal adulterant to weight loss supplements. These findings are consistent with the results of many other studies [35,36,44,45]. People who take herbal slimming preparations that contain undeclared phenolphthalein may face an increased risk of cancer [35,36,44].…”
Section: Discussionsupporting
confidence: 91%
“…This drug is often found alongside sibutramine as an illegal adulterant to weight loss supplements. These findings are consistent with the results of many other studies [35,36,44,45]. People who take herbal slimming preparations that contain undeclared phenolphthalein may face an increased risk of cancer [35,36,44].…”
Section: Discussionsupporting
confidence: 91%
“…Especially microbial safety is of high importance to include in all these studies as food pathogens like E.coli, Salmonella and Listeria can cause effects within hours after intake (Alwakeel 2009). A microbiological and pharmaceutical quality and safety assessment on over-the-counter herbal weight loss supplements in Egypt showed that, based on microbial count, 100% of the unapproved weight loss products had poor bacteriological quality (Ahmed et al, 2019). To date, the European Pharmacopoeia TCM working group has elaborated about 80 TCM herbal monographs with ISO standards for over 14 MPs published or under development.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the possible bioactive substances of the plant, the exact plant material of the product may also play an important role. Most of the adverse events (AE) of herbal products and herbal medicines can be attributed to poor quality, processing and (im)purity of the product (Ahmed et al, 2019; Chan, 2003). This stresses the need for a critical systematic review of the available data on safety of MC use in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, most people are attracted to the use of herbal weight loss products because of the faulty perception that these are safe. 39 These products may however contain FDA-banned ingredients which have many side effects that could induce heart failure, cancer, and other life-threatening conditions. 40 In addition, they contain stimulants such as caffeine that may cause insomnia, depression, addiction, suicidal thoughts, and heart attacks, which could be fatal.…”
Section: Discussionmentioning
confidence: 99%